Knowledge and risk perception of sexually transmitted infections and relevant health care services among high school students in the Platfontein San community, Northern Cape Province, South Africa - Nyasulu P; Fredericks M; Basera TJ; Broomhead S (Dove Medical Press, 2018)
Peter Nyasulu,1,2 Mercedes Fredericks,2 Tariro J Basera,2 Sean Broomhead3 1Division of Epidemiology and Biostatistics, Faculty of Medicine and Health Sciences, Stellenbosch University, Cape Town, South Africa; 2School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa; 3Health Information Systems Program, Waterkloof Ridge, Pretoria, South Africa Background: The historically marginalized Platfontein San youths have a high rate of teenage pregnancies and sexually transmitted infections (STIs). The aim of the study was to assess the knowledge and perception of male and female school-going youths in Platfontein of STIs and HIV/AIDS, and the health care services that are available to them.Participants and methods: A descriptive cross-sectional survey with a sample of 201 learners in grades 6–12 at the !Xunkwesa Combined School in Platfontein was conducted in July 2007. A pretested self-administered questionnaire was used for data collection.Results: The study found that STI knowledge was 70.1% and HIV and AIDS was 11.9%. Perceptions of risk among the learners were uniformly low; 24% for contracting a STI and 26% for HIV. About 59% (n=119) of the respondents were either unaware or not sure of the primary health care (PHC) services within the community. Overall, 65% of the students reported using PHC services while 35% exclusively used traditional healers. Slightly less than half (43%) of the learners acquired information about sexual and reproductive health through the Life Skills curriculum at school.Conclusion: The study highlights the importance of increasing HIV awareness and inculcating sexual and reproductive health into the school curriculum. The study further shows the imperative need to recognize the role of traditional medicine in the health care choices of this community. Traditional value systems need to be incorporated into the way that education and health care is proposed to the community leaders, to increase acceptance and utilization of health services. Keywords: sexually transmitted infections, school-going youths, Platfontein, knowledge, perceptions, San community